Acoustic relaxation near the isotropic liquid-nematic phase transition in the nematic phase in p-n-octyloxy p’cyanobiphenyl - DRZYMAŁA, A.; CIEŚLAK, M.; HERBA, H.; MICHALSKI, J. (Archives of Acoustics, 1992)
The paper presents the results of the completation measurements on p-n-octyloxy p’cyanobiphenyl [1] of the absorption and the ultrasonic velocity in the smectic-nematic phase for a frequency range varying from 2.5MHz to 60 MHz. In the nematic phase near the isotropic liquid-nematic transition, the contributions to the quantities αλ and α/f^2 the critical slowing down of the order parameter, the fluctuations of the order parameter and the director fluctuations were analyzed. Each ultrasonic absorption mechanism was characterized by an appropriate relaxation time near the phase transition.